Influence of El Niño–Southern Oscillation on moist static energy transport - Chae-Eun Hong; Dajeong Jeong; Ije Hur; Changhyun Yoo (Geoscience Letters)
Abstract This study investigates how El Niño–Southern Oscillation (ENSO) modulates the poleward transport of moist static energy (MSE) in the Northern Hemisphere winter. When an ENSO index increases by its one standard deviation, the MSE transport is enhanced by approximately 6% in the tropics (0°–15°N) and by 5% in the poleward of 40°N, while it is decreased by approximately 6–10% in 15°–40°N. The transport anomaly is mainly driven by changes in the mean meridional circulation associated with ENSO, with dry static energy transport being dominant over latent energy transport. In the extratropics, contributions from stationary and transient eddies are large, but tend to cancel each other out. The mean meridional transport anomaly is primarily explained by changes in the circulation, not by changes in the MSE. This contrast with the stationary transport anomaly, which consists of both circulation-driven and energy-driven changes. The transient dry static energy transport is the only component that follows the flux–gradient relationship. The study underscores the importance of changes in atmospheric circulation, rather than just energy itself, in shaping how energy is transported across latitudes during ENSO events.